Eu³⁺ and Li⁺ Co-doped SmCa₄O(BO₃)₃ phosphors: Negative thermal quenching and photoluminescence properties - Altowyan, Abeer S.; Kaynar, U.H.; Çin, E. Aymila; Karaman, T.; Aydin, H.; Coban, M.B.; Hakami, Jabir; Can, N. (Journal of alloys and compounds, 2025)
Eu³ ⁺-doped SmCa₄O(BO₃)₃ (SCOB:Eu³⁺) phosphors, with and without Li+ co-doping, were synthesized via a sol-gel combustion method and analysed for their structural and photoluminescence (PL) properties. X-ray diffraction and Rietveld refinement confirmed the monoclinic structure of the host lattice, showing that Eu³ ⁺ ions preferentially substitute Sm³ ⁺ rather than Ca²⁺, as evidenced by negligible lattice parameter variations. Quantitative analysis using the Scherrer and Williamson-Hall methods revealed reductions in crystallite size and increased lattice strain upon doping, with Li⁺ co-doping stabilizing the lattice and enhancing crystallinity. Li⁺ co-doping significantly enhances the 611 nm red emission in Eu³ ⁺-doped SCOB by reducing non-radiative losses,improving energy transfer efficiency, and modifying the local crystal field to favor radiative recombination. PL measurements demonstrated intense 611 nm emission (5D0→7F2 transition) and secondary emission at 823 nm (5D0→7F6 transition), highlighting the unique capability of the SCOB host to support magnetic dipole transitions. Bidirectional energy transfer between Eu³ ⁺ and Sm³ ⁺ ions was observed under varying excitation wavelengths, emphasizing the dynamic nature of luminescence. CIE chromaticity analysis confirmed the tunable orange-to-red emission under varying excitation wavelengths, with Li⁺ co-doping shifting the chromaticity coordinates further into the red region, optimizing the material for warm white LEDs. Temperature-dependent PL measurements demonstrated negative thermal quenching, where emission intensity increased with rising temperatures, showcasing the thermal stability of SCOB:Eu³ ⁺. The critical distance (Rₐ = 19.30 Å) for energy transfer indicated that energy migration predominantly occurs through electric multipolar interactions. SCOB:Eu³ ⁺ phosphor enhanced PL lifetime (1.18 ms), indicating high radiative efficiency and reduced non-radiative losses. These findings highlight the dual role of Li⁺ co-doping in stabilizing the lattice and enhancing photoluminescence properties, establishing SCOB:Eu³ ⁺ and SCOB:Eu³ ⁺,Li⁺ phosphors as promising candidates for thermally stable, high-efficiency red-emitting devices in solid-state lighting and photonic applications. [Display omitted] •Eu³ ⁺-doped SCOB phosphors show intense red emission at 3 wt% doping.•Li⁺ co-doping boosts photoluminescence by reducing losses and enhancing crystallinity.•Negative thermal quenching increases emission at high temperatures, ensuring stability.•CIE chromaticity shifts to red, optimizing SCOB for warm white LEDs.•Efficient energy transfer via multipolar interactions enhances luminescence.